2012
DOI: 10.2522/ptj.20110037
|View full text |Cite
|
Sign up to set email alerts
|

Personal Health Behaviors and Role-Modeling Attitudes of Physical Therapists and Physical Therapist Students: A Cross-Sectional Study

Abstract: BackgroundPhysical therapists have been encouraged to engage in health promotion practice. Health professionals who engage in healthy behaviors themselves are more apt to recommend those behaviors, and patients are more motivated to change their behaviors when their health care provider is a credible role model.ObjectiveThe purpose of this study was to describe the health behaviors and role-modeling attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 26 publications
5
36
0
Order By: Relevance
“…Recent studies have confirmed that physiotherapists should be models in PA practice in order to motivate and educate patients about the importance of a physically active lifestyle [3,4]. However, among physicians, physiotherapists are the most physically active, although according to Chevan et al, 2010, no study has described their PA habits, and in this context, our study focuses on the assessment of this aspect [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed that physiotherapists should be models in PA practice in order to motivate and educate patients about the importance of a physically active lifestyle [3,4]. However, among physicians, physiotherapists are the most physically active, although according to Chevan et al, 2010, no study has described their PA habits, and in this context, our study focuses on the assessment of this aspect [5].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies which tried to assess student attitudes towards the persons with disability [3,4], elderly [5,6], Evidence-based practice [7], inter professional education [8], personal health behaviors [9], academic dis-…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies which tried to assess student attitudes towards the persons with disability [3,4], elderly [5,6], Evidence-based practice [7], inter professional education [8], personal health behaviors [9], academic disOriginal Article honesty [10] and physical therapy assisstants [11] etc. But the attitude of physical therapy students towards their education and profession was studied only in few studies [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in the same study, under 20% of the participants reported receiving any formal training in weight management. Black, Marcoux, Stiller, Qu and Gellish (2012) even suggested that physiotherapists should discipline their own bodies to become "role models" for patients by maintaining a "healthy weight". This focus on fatness seems to follow the pattern of increasing medicalisation of weight described in the last chapter and may be based on the same dominant weight discourses.…”
Section: Intensified Focus On Weight Managementmentioning
confidence: 99%
“…Physiotherapy literature often discusses obesity as a contributing factor to disorders that physiotherapists treat, or the effects of weight change on such conditions (e.g., Black et al, 2012;Woolner & Dean, 2013). However, the relevance of body weight to the conditions that physiotherapists often treat is far from unequivocal.…”
Section: Intensified Focus On Weight Managementmentioning
confidence: 99%